2003
DOI: 10.1029/2003ja009997
|View full text |Cite
|
Sign up to set email alerts
|

Toward a solution to the early faint Sun paradox: A lower cosmic ray flux from a stronger solar wind

Abstract: [1] Standard solar models predict a solar luminosity that gradually increased by about 30% over the past 4.5 billion years. Under the faint Sun, Earth should have been frozen solid for most of its existence. Yet, running water is observed to have been present since very early in Earth's history. This enigma is known as the faint Sun paradox. We show here that it can be partially resolved once we consider the cooling effect that cosmic rays are suspected to have on the global climate and by considering that the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 53 publications
0
37
0
Order By: Relevance
“…If there had been less land early in Earth's history and more zonally uninterrupted ocean, one might expect there to have been more cloud rather than less (similar to how there is greater cloud fraction in the Southern Hemisphere than the Northern Hemisphere). Also relating to low cloud, Shaviv (2003) and Svensmark (2007) contend that fewer galactic cosmic rays were incident on the troposphere during the Archean and this would have led to less stratus. However, the underlying hypothesis for this has been refuted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If there had been less land early in Earth's history and more zonally uninterrupted ocean, one might expect there to have been more cloud rather than less (similar to how there is greater cloud fraction in the Southern Hemisphere than the Northern Hemisphere). Also relating to low cloud, Shaviv (2003) and Svensmark (2007) contend that fewer galactic cosmic rays were incident on the troposphere during the Archean and this would have led to less stratus. However, the underlying hypothesis for this has been refuted.…”
Section: Discussionmentioning
confidence: 99%
“…Sun and Bradley, 2002;Lockwood and Fröhlich, 2007;Kristjánsson et al, 2008;Bailer-Jones, 2009;Calogovic et al, 2010;Kulmala et al, 2010, and references therein): galactic cosmic rays cause the formation of at most 10% of CCNs and there is no correlation between galactic cosmic ray incidence and cloudiness. Also of note is that Shaviv (2003) requires a highly non-standard climate sensitivity to force his model. In the sensitivity test where he uses a more standard climate sensitivity, it results in a mean temperature ∼0 • C during the Archean.…”
Section: Decreased Stratusmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of this, many researchers have serious reasons (Carslaw, 2009) to consider that galactic cosmic rays (GCR) play one of the key roles in the mechanisms of the weather and the climate formation in our planet (Carslaw, 2009;Marsh and Svenmark, 2000;Svensmark and Calder, 2007;Stozhkov, 2003;Usoskin et al, 2004;Shaviv, 2002Shaviv, , 2003Shaviv, , 2003a.…”
Section: Introductionmentioning
confidence: 99%
“…This paradox states that geological records indicate that water existed in liquid form very early in the history of Earth despite the young Sun having only 70% of its current luminosity. Shaviv (2003) suggested that this discrepancy can be explained by a significantly stronger solar wind. Since the winds and outflows are magnetically driven phenomena in Sun-like stars, a correlation with the magnetic field is expected.…”
Section: Introductionmentioning
confidence: 99%